The Effects of Intercropping with Four Tropical Legume Species on the Yield and Quality of Napier Grass in Thailand - Pornthip Anantawiroon; Sayan Tudsri; Yasuyuki Ishii; Suwapong Sawadihpanich; Somboon Tachaboonyapiwat (Agriculture and Natural Resources, 2006)
A comparison of yield and quality of napier Taiwan A25 (Pennisetum purpureum) intercropped with four different legume species (Cajanus cajan, Crotalaria juncea, Leucaena leucocephala and Sesbania luteola) was carried out at the National Corn and Sorghum Reseaech Center, Pakchong district, Nakornratchasima, Thailand, over a 12-month period. The objective was to determine the optimal combination of legume species and the proportion of grass/legume in napier fodder banks in Thailand. The design of the experiment was a split plot with legume species as the main plot and the ratio between rows of grass and legume (1 : 1, 1 : 2 and 1 : 4) as sub – plot. The results showed that crotalaria produced the highest total dry matter yield followed by leucaena, pigeon pea and sesbania. Grass yield was highest in the crotalaria plots and lowest in the leucaena plots. Thus, the total dry matter yield (grass + legume) was highest in the crotalaria plots and lowest in the leucaena plots. However, sesbania and crotalaria produced substantial yields only during the first two cuts with yields declining dramatically. Increasing the ratio between grass and legume resulted in a greater legume yield. The recommendation for the ratio between grass and legume was 1 : 2 (1 row grass : 2 rows legume).